Religiosidade, espiritualidade, ansiedade, depressão e bem-estar subjetivo de pacientes submetidos à cineangiocoronariografia - LIMA JÚNIOR, José de Ribamar Medeiros (2021)
Introduction: Cardiovascular diseases are among the main causes of mortality in the world, and understanding new treatment strategies is very important. Anxiety and depression are also pathologies that have added efforts to better understand and treat them. Religiosity and spirituality and the possibilities of using them to fight diseases have gained ground in society. Objective: To analyze the relationship between religiosity and spirituality and religious-spiritual coping, anxiety and depression, as well as to assess the subjective well-being in patients with Coronary Artery Disease. Method: Analytical, cross-sectional study with a quantitative approach, which was carried out at the University Hospital of the Federal University of Maranhão (HUUFMA). The study period was from March 2019 to August 2019. Data collection was performed using the following instruments, a socioeconomic and demographic questionnaire, the Duke Religiosity Index, the CRE-Breve scale (Religious-Spiritual Coping) and the scale of HADS to obtain the results. Results: The study totaled 148 patients, of these 80 patients (54.05%) were female, the mean age of patients with greater expressiveness was in the score between 61-70 years (22.97%), we had an Organizational Religiosity (RO) with the vast majority answering that they attend once a week, totaling 30.41%; a Non-Organizational Religiosity (RNO) of 82.43% who dedicate their time to individual religious activities, and an Intrinsic Religiosity (IR) expressed by 90.54% where the presence of God or the Holy Spirit in the lives of respondents is totally true. A total of 58.78% had a diagnosis of CAD. As for the HADS-A (Anxiety), 41.89% have the possibility of having an anxiety condition with a p-value of 0.917, as for the subscale; HADS-D (Depression) presents 62.84% with p-value of 0.307 that has the possibility of having a picture of depression. When quantifying BES, it was identified that more than half of the participants had a high level of BES. When CAD was associated with BES, a p-value of 0.398 was obtained, demonstrating that, regardless of the CAD diagnosis, there was no association between Subjective Well-being (BES) and Coronary Artery Disease. Conclusion: Although there was no relationship between CAD and the study variables, the study's contribution to better understanding and attention to multidisciplinary and integrative approach strategies to aid in coping with chronic diseases, especially psychiatric ones, and involvement with aspects of religiosity and spirituality, supporting further investigations and research on this theme.